Body fat differences by self‐reported race/ethnicity in healthy term newborns. Issue 5 (28th October 2015) - Paley, C.; Hull, H.; Ji, Y.; Toro‐Ramos, T.; Thornton, J.; Bauer, J.; Matthews, P.; Yu, A.; Navder, K.; Dorsey, K.; Gallagher, D.
Summary: Background: Ethnic differences in total body fat (fat mass [FM]) have been reported in adults and children, but the timing of when these differences manifest and whether they are present at birth are unknown. Objectives: This study aimed to assess whether ethnic differences in body fat are present at birth in healthy infants born at term, where body fat is measured using air displacement plethysmography and fat distribution by skin‐fold thickness. Methods: Data were from a multiracial cross‐sectional convenience sample of 332 term infants from four racial or ethnic groups based on maternal self‐report (A, Asian; AA, non‐Hispanic Black [African‐American]; C, non‐Hispanic White; and H, Hispanic). The main outcome measure was infant body fat at 1–3 days after birth, with age, birth weight, gestational age and maternal pre‐pregnancy weight as covariates. Results: Significant effects for race ( P = 0.0011), sex ( P = 0.0051) and a race by sex interaction ( P = 0.0236) were found. C females had higher FM than C males ( P = 0.0001), and AA females had higher FM than AA males ( P = 0.0205). C males had less FM than A males ( P = 0.0353) and H males ( P = 0.0001). Conclusion: Race/ethnic and sex differences in FM are present in healthy term newborns. Although the implications of these differences are unclear, studies beginning in utero and birth set the stage for a life course approach to understanding disease later in life.